Diagnostic radiology in disaster medicine: implications for design, planning and organization of X-ray departments - Eldar, R.; Inbar, A (Injury, 1987)
Diagnostic radiology plays an important role in the evaluation of disaster casualties; these are referred to X-ray departments, shortly after their arrival at hospital, in large numbers, frequently overwhelming facilities and resources of the department. The study of relevant literature and the experience of the authors suggest that there are implications for design, planning and organization of X-ray departments to be considered in disaster-prone areas. Departments should be sited as near as possible to triage areas, on the same floor, with broad, unobstructed passages. There should be provision for easy passage of equipment and trolleys through doors and corridors and large circulation areas, working rooms and waiting spaces with plugs, for electricity, piped oxygen and suction and devices for hanging infusion sets. Two entrances to the department would enable one-way flow through the department. All work should be done in the department and examinations performed with mobile units avoided. A radiologist at the entrance to the department and a control post at the exit ensure adequate processing of casualties. Interpretation and reporting should be done by assigned radiologists dictating directly to typists; films and reports should accompany casualties.